MENUJU PENINGKATAN KESEJAHTERAAN EKONOMI: MENGGALI PERAN LEMBAGA KEUANGAN MIKRO SYARIAH - Andriansyah, Andriansyah; Sukri, Muhammad; Nirwana, Nirwana (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
Economic empowerment through Sharia micro-institutions constitutes a crucial aspect of national economic development and growth. Providing Sharia-compliant financial institutions that offer financing to community enterprises based on profit-sharing principles is a key strategy in achieving economic self-sufficiency. This study aims to delve into the role of Sharia financial institutions in bolstering community economic empowerment, particularly in rural areas. Employing a descriptive qualitative method with a library research approach, this research uncovers that Sharia financial institutions serve as crucial entities in furnishing various facilities and products to rural communities for financing their informal sector businesses, adhering to Sharia principles. The evolution of Sharia financial institutions fosters economic self-reliance among rural communities, consequently impacting national economic development and growth. The involvement of Sharia financial institutions in community economic endeavors, particularly in fostering the economic independence of rural communities, encompasses asset transfers, transactions, liquidity management, and enhancing efficiency. The existence of Sharia financial institutions serves as a catalyst for rural communities to enhance the productivity of their businesses, thereby facilitating community economic empowerment and actualizing community welfare as an integral part of the national economic development strategic blueprint